0554 Efficacy Of Dental Device For Treatment For Moderate To Severe Obstructive Sleep Apnea In Korean: Interim Result Of Prospective Multi-center Study. (27th April 2018) - Shin, Y; Byun, J; Ahn, S; Yang, K; Cho, Y; Shin, W
Abstract: Introduction: Dental device is an effective treatment option for mild to moderate obstructive sleep apnea (OSA) patients. It is also recommended for severe OSA patient when they fail continuous positive airway pressure (CPAP) treatment. However, the effect has not been properly evaluated in Korean OSA patients. Moreover, efficacy of the dental device for severe OSA patients has not been elucidated. Methods: This was a prospective study performed at three sleep centers in Korea (Keimyung University Dongsan Medical center, Soon Chun Hyang University hospital Cheonan, and KyungHee University Hospital at Gangdong). Adult OSA patients with moderate to severe severity (AHI≥15) were recruited. They were treated with customized two-piece dental device. Sleep questionnaire and video-polysomnography were performed before and 1 month after the treatment. The primary outcome measure was improvement in apnea-hypopnea index (AHI) at 1 month after the dental device. Secondary end-points were improvement of sleep questionnaire and sleep structure. Results: Total 32 patients were enrolled between Mar 2017 and Dec 2017. Mean age was 46 ± 12.6, and 31 (93.9%) were male with mean BMI of 26.4 ± 3.7. Mean AHI was 30.1 ± 13.7. Fifteen of the patients had moderate OSA and the rest had severe OSA (AHI≥30). Follow-up PSG was performed in 22 of the patients. Mean AHI significantly improved (pre: 26.2 ± 13.0, post 9.1 ± 8.1, p<0.0001) after the dental device. The proportion of deep sleep increased (pre: 10.7 ± 12.1, post 15.1 ± 13.7, p=0.01), and N1 sleep decreased (pre: 22.3 ± 10.9, post 14.3 ± 6.9, p=0.001) with improvement in insomnia severity index (pre: 11.2 ± 5.7, post 8.4 ± 5.4, p=0.005), and Beck depression inventory (pre: 12.2 ± 12.4, post 8.2 ± 8.6, p=0.006). Conclusion: The result of this study shows that dental device may be effective in moderate to severe OSA patients. It also improves sleep structures and sleepiness and depressive symptoms. Support (If Any): None.